2000
DOI: 10.1128/iai.68.9.5011-5017.2000
|View full text |Cite
|
Sign up to set email alerts
|

Toxoids of Streptococcal Pyrogenic Exotoxin A Are Protective in Rabbit Models of Streptococcal Toxic Shock Syndrome

Abstract: Streptococcal pyrogenic exotoxins (SPEs) are superantigens that have been implicated in causing streptococcal toxic shock syndrome (STSS). Most notably, SPE serotype A is made by nearly all M-protein serotype 1 and 3 streptococci, the M types most associated with the illness (these strains contain one or more other SPEs, and those proteins are likely also to contribute to disease). We have prepared double-, triple-, and hexa-amino-acid mutants of SPE A by PCR and other mutagenesis procedures. The sites chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 36 publications
0
36
1
Order By: Relevance
“…Serial 10-fold dilutions of rSPE J (beginning at 10 g/well) were added to the wells, and each dilution was assayed in quadruplicate; control wells received lymphocytes only. Equivalent concentrations of purified SPE A or SPE C prepared as previously described (38,50) were added to the wells for comparison. Plates were incubated at 37°C for 72 h in 7% CO 2 , and then 1 Ci of [ 3 H]thymidine (Amersham Corp., Arlington Heights, Ill.) was added to each well.…”
Section: Methodsmentioning
confidence: 99%
“…Serial 10-fold dilutions of rSPE J (beginning at 10 g/well) were added to the wells, and each dilution was assayed in quadruplicate; control wells received lymphocytes only. Equivalent concentrations of purified SPE A or SPE C prepared as previously described (38,50) were added to the wells for comparison. Plates were incubated at 37°C for 72 h in 7% CO 2 , and then 1 Ci of [ 3 H]thymidine (Amersham Corp., Arlington Heights, Ill.) was added to each well.…”
Section: Methodsmentioning
confidence: 99%
“…The massive release of inflammatory cytokines is one of the reasons for immune-mediated fever by SEs (Roggiani et al, 1997). Our results indicated that SEC(14-128) minimally induced mouse T-cells to secrete IL-2 and IFN-c in vitro.…”
Section: Discussionmentioning
confidence: 60%
“…To decrease the chances that this protein will have any superantigenicity in vivo, the binding sites for all three factors known to bind SPEA have been mutated: TCR (N20D), MHC (L42A), and Zn 2ϩ (D77A). Other combinations of mutations in SPEA were also found by Roggiani et al [5] to provide good protection, using a rabbit model and potentiation with endotoxin.…”
Section: Discussionmentioning
confidence: 88%
“…The naturally occurring substitution V76I, known as the SPEA3 allele [13], has been shown to possess an eightfold higher affinity for HLA-DQ than SPEA1 [7,8]-even though it is not located at the predicted MHC-binding surface. Residues N20 [5,14] and L24 have been predicted to be at or near the TCR interaction surface, while residue L42 is believed to be located in the SPEA contact site for MHC class II molecules [7,8]. Residue N20 is observed to contact the TCR ␤ chain in the structure of Sundberg et al (2002) [9].…”
Section: Subject Termsmentioning
confidence: 99%
See 1 more Smart Citation